The common HAQ STING variant impairs cGAS-dependent antibacterial responses and is associated with susceptibility to Legionnaires’ disease in humans - Ruiz-Moreno, Juan S.; Hamann, Lutz; Shah, Javeed A.; Verbon, Annelies; Mockenhaupt, Frank P.; Puzianowska-Kuznicka, Monika; Naujoks, Jan; Sander, Leif E.; Witzenrath, Martin; Cambier, John C.; Suttorp, Norbert; Schumann, Ralf R.; et al. (PLoS pathogens, 2018)
The cyclic GMP-AMP synthase (cGAS)-STING pathway is central for innate immune sensing of various bacterial, viral and protozoal infections. Recent studies identified the common HAQ and R232H alleles of TMEM173/STING, but the functional consequences of these variants for primary infections are unknown. Here we demonstrate that cGAS- and STING-deficient murine macrophages as well as human cells of individuals carrying HAQ TMEM173/STING were severely impaired in producing type I IFNs and pro-inflammatory cytokines in response to Legionella pneumophila, bacterial DNA or cyclic dinucleotides (CDNs). In contrast, R232H attenuated cytokine production only following stimulation with bacterial CDN, but not in response to L. pneumophila or DNA. In a mouse model of Legionnaires' disease, cGAS- and STING-deficient animals exhibited higher bacterial loads as compared to wild-type mice. Moreover, the haplotype frequency of HAQ TMEM173/STING, but not of R232H TMEM173/STING, was increased in two independent cohorts of human Legionnaires' disease patients as compared to healthy controls. Our study reveals that the cGAS-STING cascade contributes to antibacterial defense against L. pneumophila in mice and men, and provides important insight into how the common HAQ TMEM173/STING variant affects antimicrobial immune responses and susceptibility to infection. ClinicalTrials.gov DRKS00005274, German Clinical Trials Register.